Penerapan PSAK 107 Pada Pembiayaan Gadai Syariah (Studi Kasus KSPPS BMT NU Jawa Timur Cabang Tlogosari Bondowoso) - Amir Amir; Siti Faizeh (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2024)
BMT is a financial institution in the form of a cooperative or non-governmental organization. One of the products offered at BMT is sharia pawn financing. Sharia pawning in Islam is known as rahn, which is a term in accordance with the Al-Qur'an, specifically in Surah Al-Baqarah 283. Sharia pawn financing transactions in their operations will certainly not be separated from the accounting recording process. So that it can produce accurate and relevant accounting measurements. The aim of this research is to determine the application of sharia pawn financing and to determine the suitability of the application of sharia pawn accounting at KSPPS BMT NU East Java Tlogosari Bondowoso Branch with PSAK 107. This research uses qualitative research methods with a descriptive approach, and the type of research carried out is field research using data collection techniques in the form of: observation, interviews and documentation. The validity of the data used in this research is: data source triangulation and theory triangulation. The research results show that the suitability of implementing PSAK 107 at KSPPS BMT NU East Java Tlogosari Bondowoso Branch regarding recognition, measurement and presentation is in accordance with PSAK 107, while in terms of disclosure it is not yet in accordance with PSAK 107 because there are no specifications related to financial statements in the disclosure.